Mineral Composition of Vegetable Biomass of Amaranthus L. Species - Andrushchenko, Olena (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
The mineral composition is explored of the four species of Amaranthus L.: A. lividus L., A. tricolor L., A. acutilobus Uline et W. L. Bray, and A. blitoides S. Wats. The leaves were analyzed when the plants were in the vegetative phase of development. The element concentrations determined by techniques of atomic absorption spectrometry with inductively coupled plasma spectrometry. The order of the elements is as follows: A. acutilobus, A. lividus: К>Са>Mg>S>P>Fe>Al>Na>Zn>Mn>B>Ba>Ni>Pb>V>Cd>Cr; A. blitoides: К>Са>Mg>S>P>Fe> Al>Na>Zn>Mn>Ba>B>Ni>Pb>V>Cd>Cr; A. tricolor: К>Са>S>Mg>P>Fe>Al>Na>Zn>Mn>B>Ba> Ni>Pb>V>Cd>Cr. Potassium is the main ash element in the leaves of all studied species of Amaranthus. Its content varied from 39010.00 to 44926.67 mg kg-1. A. tricolor is significantly different among other species for the ratio of sulfur and magnesium. In its leaves, a large amount of sulfur is found. The species with ascending stems (A. acutilobus and A. blitoides) contained sulfur up to 4020.00 and species with erect stems (A. lividus and A. tricolor) within 5724.00–6314.40 mg kg-1. Maximum content of Mg was 6734.33, P 1706.33, Fe 1133.28 mg kg-1. The content of heavy metals was in a safe quantity, except nickel. The highest coefficients of variation (%) are characteristic of the content of barium (45.07), sodium (31.18), vanadium (28.22) and potassium (26.62). The most stable is the content of phosphorus (3.25 %). The mineral composition of leaves of amaranth showed its high value as a vegetable product.